Model of international scientific and technical cooperation in the context of globalization and development of territories - Zhura, Svetlana; Ershova, Irina; Savelev, Ivan; Bogdanova, Elena; Teterin, Alexander; Chertova, Nadezhda (Nexo Revista Científica, 2022)
Currently a great number of problems have accumulated regarding the Arctic agenda in international legal, military, socio-economic, environmental, and scientific spheres. The authors of the study believe that international collaboration in the scientific and technical sphere, built upon a legal basis, is the first direction of mutually beneficial interstate collaboration in the Arctic region. The development of international scientific and technical collaboration in the field of complex Arctic study presupposes a comprehensive approach with regard to economic, legal and political aspects, and analyzing static and dynamic indicators. Thus, it is necessary to develop a legal model of collaboration. The development of the legal model of international scientific and technical collaboration in the field of complex Arctic study involves a range of actions aimed at improving the regulatory and conceptual framework, changing the system of state management of scientific and technical collaboration in the Arctic zone in order to ensure a consistent policy and eliminate existing problems.